Given f(x) = radical x-2 and g(x) = x2 – x – 6. Find (g o f)(6).

A. -4
B. 2
C. 24
D. 26
E. 48

1 answer

g(f) = f^2 - f - 6
= (x-2) - √(x-2) - 6

g(f(6)) = 4 - 2 - 6 = -4
Similar Questions
  1. Find the area of the rectangle shown in the figure.length = radical (3) + radical (5) width = radical (3) + radical (5) My
    1. answers icon 0 answers
  2. Simplify by combining like terms.Problem #32 radical (63) - 2 radical (28) + 5 radical (7) My answer: 4radical(7) Problem #50
    1. answers icon 0 answers
  3. Find the domain of the following functions.1. y= radical(x-3) - radical(x+3) 2. y= [radical(2x-9)] / 2x+9 3. y= radical(x^2 - 5x
    1. answers icon 1 answer
  4. solve the equation or formula for the indicated variable R=ts^2+3a)s=under radical R-3/t (not under radical b)s=everything under
    1. answers icon 2 answers
more similar questions